Structural change and wage inequality: Evidence from German micro data - Philipp Henze (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
This paper measures the impact of sectoral composition, international trade and technological progress on the rising wage gap in Germany. I find a positive effect of the increasing importance of services on the rising wage gap in Germany that is comparable to the effects of international trade and technological change. To quantify the causal relationship between the structural change of the German economy and the wage premium, I use the Establishment History Panel (in German: Betriebs-Historik-Panel - BHP), a detailed establishment-level data set provided by the German Federal Employment Office covering the period 1975-2010. This empirical work puts the focus on an important cause of the rising wage gap that so far has been largely ignored by the literature.
Keywords: F16; J31; O15; O30; 330; income inequality; structural change; international trade; technological change